Blood research of Simmental breed animals in the Carpathian region - V. D. Fedak; O. I. Stadnytska; B. V. Gutyj; M. I. Polulikh; N. V. Nazaruk; O. О. Bezaltychna; A. P. Kitaeva; V. M. Dovgopolov; N. Yu. Kibenko; O. B. Shevchenko; V. Ya. Binkevych; N. O. Kravchenko (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки)
Physiological and biochemical blood parameters in Simmental heifers in postnatal ontogenesis of different types of constitution are presented. The physiological and selection index was calculated on the basis of digital indicators of the intensity of transamination enzymes and body weight of heifers in the corresponding periods of growth. It is shown that at the age of 6 months it is possible to assess the young, in this case heifers, by the type of constitution. The number of erythrocytes in the blood of heifers at 6, 12, 18 months old in the experimental group was higher than that of the control ones by 4.25; 9.91; 9.82 %, respectively. On average, over the entire period of rearing, the animals of the experimental group exceeded the control counterparts by 7.92 %. In terms of hemoglobin content in the blood, the experimental heifers at the ages of 6, 12, 18 months exceeded the control counterparts by 8.20; 10.83; 10.90 %, respectively. On average, over the entire period of rearing, the animals of the experimental group exceeded the control counterparts by 7.64 %. In terms of total protein content in the blood serum, the heifers at the ages of 6, 12, 18 months old in the experimental group exceeded the control counterparts by 7.47; 15.23; 8.64 %. On average, over the entire growing period, the animals of the experimental group outnumbered the control counterparts by 8.09 %. Another important indicator, which also characterizes protein metabolism in the animal body, is the activity of aminotransferases in the blood serum. In terms of AST activity in the blood serum, on average over the entire period of growing animals, the experimental group exceeded the control group by 11.78 %. A similar pattern was found in terms of ALT activity in the blood serum. Thus, the heifers of the experimental group in terms of ALT activity in the blood serum at 6, 12, 18 months old exceeded the control peers by 4.72; 8.13; 8.01; 10.28 %, respectively. In terms of the content of total sulfhydryl groups in the blood of heifers of the experimental group at 6, 12, 18 months, they were superior to the control analogues by 10.85; 27.50; 23.44; 18.01 %, respectively. In terms of the content of residual SH-groups in the blood of animals of the experimental group in postnatal ontogenesis, they were superior to the control analogues by 24.34 %. Experimental heifers in terms of total glutathione content at the age periods of 6, 12, 18 months old exceeded control counterparts by 8.38; 20.25; 7.44; 5.48 %, respectively. A similar pattern was observed in terms of reduced glutathione content in the blood of experimental animals. Thus, in terms of reduced glutathione content in the blood of individuals of the experimental group for the entire period of cultivation, they exceeded control peers by an average of 9.56 %.